2012
DOI: 10.5120/ijais12-450135
|View full text |Cite
|
Sign up to set email alerts
|

Odia Text Summarization Using Stemmer

Abstract: Lot of work has already been done for automatic text summarization. In this paper we have given a novel statistical approach to summarize the given Odia text. In our approach extraction of relevant sentences is done which can give the actual concept of the input document in a concise form. We rank each sentence in the document by assigning a weight value to each word of the sentence. The sentences are extracted as per their rank, which will lead to a good summary of the given text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…al. has done the summarization by using an Odia stemmer [3]. In their work they take a part of the text as for their implementation, first, they had tokenized the whole text and in the second step, they remove the stop words.…”
Section: Related Workmentioning
confidence: 99%
“…al. has done the summarization by using an Odia stemmer [3]. In their work they take a part of the text as for their implementation, first, they had tokenized the whole text and in the second step, they remove the stop words.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly considering applicability of clustering one of the method used by the proposed model, has always been effective in removing redundancy [Oufaida et al (2014) Considering Odia language, limited research on the discussed topic has been reported. A summarizer [Balabantaray et al (2012)] based on normalized frequency count of the content words (exclusive of stop words) for determining significant sentences has claimed an average accuracy of 61%. The first sentence of the document has been mandatorily included in the summary giving importance to sentence position in the input document and compression ratio is kept at 50%.…”
Section: Related Workmentioning
confidence: 99%
“…R.C.Balabantaray have worked on Odia text summarization using stemmer. A novel statistical approach has been applied to summarize the given Odia text [19].…”
Section: Literature Surveymentioning
confidence: 99%